Disappearing cryptography information hiding : steganography & watermarking - Wayner, Peter, 1964- (Amsterdam ; Boston : MK/Morgan Kaufmann Publishers, 2002)
Disappearing Cryptography, Second Edition describes how to take words, sounds, or images and hide them in digital data so they look like other words, sounds, or images. When used properly, this powerful technique makes it almost impossible to trace the author and the recipient of a message. Conversations can be submerged in the flow of information through the Internet so that no one can know if a conversation exists at all. This full revision of the best-selling first edition describes a number of different techniques to hide information. These include encryption, making data incomprehensible; steganography, embedding information into video, audio, or graphics files; watermarking, hiding data in the noise of image or sound files; mimicry, "dressing up" data and making it appear to be other data, and more. The second edition also includes an expanded discussion on hiding information with spread-spectrum algorithms, shuffling tricks, and synthetic worlds. Each chapter is divided into sections, first providing an introduction and high-level summary for those who want to understand the concepts without wading through technical explanations, and then presenting greater detail for those who want to write their own programs. To encourage exploration, the author's Web site www.wayner.org/books/discrypt2/ contains implementations for hiding information in lists, sentences, and images. Each chapter is divided into sections, providing first an introduction and high-level summary for those who want to understand the concepts without wading through technical details, and then an introductory set of details, for those who want to write their own programs. Fully revised and expanded. Covers key concepts for non-technical readers. Goes into technical details for those wanting to create their own programs and implement algorithms. Up-to-date website containing the code samples from the book.
Preface. Framing Information. Encryption. Error Correction. Secret Sharing. Compression. Basic Mimicry. Grammars and Mimicry. Turing and Reverse. Life in the Noise. Anonymous Remailers. Secret Broadcasts. Keys. Ordering and Reordering. Spreading. Synthetic Worlds. Watermarks. Steganalysis. Afterword. Appendix A Java Mimic Code. Appendix B Baseball CFG. Appendix C Reversible Grammar Generator. Appendix D Software. Further Readings. Bibliography. Index.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures; Cryptography; Internet; Digital watermarking; Electronic books